Peran Knowledge Management Terhadap Sustainable Competitive Advantage Melalui Dynamic Capabilities Pada Perguruan Tinggi Swasta di Garut - Fikar Raysona, Mochamad; Aulawi, Hilmi; Aisyah, Risa (Institut Teknologi Garut, 2025)
This study aims to analyze the role of knowledge management in achieving sustainable competitive advantage at Private Universities (PTS) in Garut, by examining both its direct and indirect effects through dynamic capabilities as a mediating variable. The main issues in this context are the weak implementation of systematic knowledge management practices, the lack of a collective knowledge-sharing culture, and the suboptimal integration of information technology to support knowledge transfer and application in the academic environment. The research employs a quantitative approach by distributing questionnaires to 151 permanent lecturers as respondents. Data processing was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4.0 application. The results indicate that knowledge management has a direct and significant influence on sustainable competitive advantage. However, this influence becomes stronger when mediated by dynamic capabilities, which consist of the institution’s abilities in sensing, seizing, and transforming organizational resources. The path coefficient values for the indirect effect through dynamic capabilities are also significant, underscoring the importance of integrating knowledge management systems with dynamic capabilities to strengthen institutional competitiveness. Furthermore, model testing shows that the structural model used demonstrates high explanatory and predictive power, with R-square and Q-square values categorized as very good. The study concludes that strategies to enhance the competitiveness of private universities should be directed toward strengthening a knowledge-based strategy that emphasizes organizational learning, innovation, and adaptive institutional capabilities. These findings provide both theoretical and practical contributions for higher education management in designing sustainable, knowledge-based strategies.